Selection in Early Generations to Shift Allele Frequency for Seminal Root Angle in Wheat. Issue 2 (1st July 2018) - Richard, Cecile; Christopher, Jack; Chenu, Karine; Borrell, Andrew; Christopher, Mandy; Hickey, Lee
Abstract : A current challenge for plant breeders is the limited ability to phenotype and select for root characteristics to enhance crop productivity. The development of a high‐throughput phenotyping method has recently offered new opportunities for the selection of root characteristics in breeding programs. Here, we investigated prospects for phenotypic and molecular selection for seminal root angle (SRA), a key trait associated with mature root system architecture in wheat ( Triticum aestivum L.). We first investigated genetic diversity for this trait in a panel of 22 wheat lines adapted to Australian environments. The angle between the first pair of seminal roots ranged from 72 to 106°. We then evaluated selection gain via direct phenotypic selection in early generations by comparing the resulting shift in population distribution in tail populations selected for "narrow" and "wide" root angle. Overall, two rounds of selection significantly shifted the mean root angle as much as 10°. Furthermore, comparison of allele frequencies in the tail populations revealed genomic regions under selection, for which marker‐assisted selection appeared to be successful. By combining efficient phenotyping and rapid generation advance, lines enriched with alleles for either narrow or wide SRA were developed within only 18 mo. These results suggest that there is a valuable source of allelic variation for SRA that can be harnessed and rapidly introgressed into elite wheat lines.